ResSeg: Residual encoder-decoder convolutional neural network for food segmentation - Javier O. Pinzón-Arenas; Robinson Jiménez-Moreno; César G. Pachón-Suescún (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This paper presents the implementation and evaluation of different convolutional neural network architectures focused on food segmentation. To perform this task, it is proposed the recognition of 6 categories, among which are the main food groups (protein, grains, fruit, vegetables) and two additional groups, rice and drink or juice. In addition, to make the recognition more complex, it is decided to test the networks with food dishes already started, i.e. during different moments, from its serving to its finishing, in order to verify the capability to see when there is no more food on the plate. Finally, a comparison is made between the two best resulting networks, a SegNet with architecture VGG-16 and a network proposed in this work, called Residual Segmentation Convolutional Neural Network or ResSeg, with which accuracies greater than 90% and interception-over-union greater than 75% were obtained. This demonstrates the ability, not only of SegNet architectures for food segmentation, but the use of residual layers to improve the contour of the segmentation and segmentation of complex distribution or initiated of food dishes, opening the field of application of this type of networks to be implemented in feeding assistants or in automated restaurants, including also for dietary control for the amount of food consumed.